QUALITY FORMATION OF THE SURFACE WATERS WITHIN LUTSK - Мисковець, Ірина; Мольчак, Ярослав (Modern engineering and innovative technologies, 2023)
The paper analyzes the ecological state of surface waters of the Lutsk town and its usage. The article highlights the main reasons for their deterioration. An analysis of the natural and anthropogenic influence on the process of formation of surface wate